2010
DOI: 10.1074/jbc.m110.102640
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domains of L-selectin and CD44 Regulate Receptor Cell Surface Positioning and Leukocyte Adhesion under Flow

Abstract: During inflammation and immune surveillance, initial contacts (tethering) between free-flowing leukocytes and the endothelium are vitally dependent on the presentation of the adhesion receptor L-selectin on leukocyte microvilli. Determinants that regulate receptor targeting to microvilli are, however, largely elusive. Therefore, we systematically swapped the extracellular (EC), transmembrane (TM), and intracellular (IC) domains of L-selectin and CD44, a hyaluronan receptor expressed on the cell body and exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 45 publications
0
28
1
1
Order By: Relevance
“…By contrast, leukocyte rolling velocity was not affected by the topographic distribution of L-selectin (34,35). Most probably, the impairment of leukocyte tethering observed in our study (Figs.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…By contrast, leukocyte rolling velocity was not affected by the topographic distribution of L-selectin (34,35). Most probably, the impairment of leukocyte tethering observed in our study (Figs.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies performed with transfectants expressing chimeric L-selectin/CD44 molecules demonstrated that leukocyte tethering on endothelium (34) or PSGL-1 (35) is dependent on the distribution of L-selectin on leukocyte microvilli (34,35) and on the binding of L-selectin cytoplasmic domain to ERMs and actin cytoskeleton (35). By contrast, leukocyte rolling velocity was not affected by the topographic distribution of L-selectin (34,35).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…An extensive process referred to as 'Rolling-Adhesion -Transmigration' is responsible for neutrophil migration out of circulation to sites of infection or inflammation. The 'Rolling' step refers to the initial attachment of neutrophils to the endothelial cells and occurs when cells are stimulated with cytokines produced during an infection such as TNF-α, IL-1β, and interleukin 7 (IL-7) (74,(97)(98)(99). This chemokine production stimulates expression of selectins (P-and E-selectin), integrins such as intracellular adhesion molecules (ICAMs) and vascular cell adhesion molecules (VCAMs) on the luminal surface of the endothelial cells which can bind to the selectin and integrin ligands located on the neutrophils (74,98,100).…”
Section: Fusobacterium Nucleatum (F Nucleatum) and Aggregatibacter mentioning
confidence: 99%